2019
DOI: 10.3390/nu11071605
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Diet Diversity in Eight Latin American Countries: Results from the Latin American Study of Nutrition and Health (ELANS)

Abstract: This study aimed to assess diet quality score (DQS), considering healthy and unhealthy foods and nutrients, and diet diversity score (DDS) as indicators of risk of noncommunicable diseases in eight Latin American countries, and to verify the possible differences considering country, sex, age, socioeconomic, and nutritional status. A multicenter household population-based cross-sectional survey was conducted with 9218 individuals (age range 15–65 years). Sociodemographic and anthropometric data were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 57 publications
3
35
0
5
Order By: Relevance
“…Overall, dietary diversity was very low. Gomez et al (2019), a study of eight Latin American countries, found that other countries have much more diverse diets with DDS scores of five to six (out of nine) [15]. They found a slightly higher mean score in Venezuela than this analysis (5.62 of 9 compared to 2.3 of 8), but their study was conducted in only urban areas and during an earlier time period (2014-2015) than EVESCAM (2014-2017) which may have been affected by the onset of the humanitarian crisis in Venezuela.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, dietary diversity was very low. Gomez et al (2019), a study of eight Latin American countries, found that other countries have much more diverse diets with DDS scores of five to six (out of nine) [15]. They found a slightly higher mean score in Venezuela than this analysis (5.62 of 9 compared to 2.3 of 8), but their study was conducted in only urban areas and during an earlier time period (2014-2015) than EVESCAM (2014-2017) which may have been affected by the onset of the humanitarian crisis in Venezuela.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the crisis, the burdens of T2D, hypertension, and obesity were documented to be increasing over time, particularly in urban areas [ 13 , 14 ]. However, few studies have looked at recent dietary intake in Venezuela [ 15 , 16 ] and most of these have been limited to convenience samples rather than nationally representative data. Furthermore, NCD burden has been especially hard to quantify over the past few years, as the Venezuelan government has stopped publishing national statistics since 2016 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the countries we studied still face significant rural-to-urban migration, which could be linked to high obesity risk [51]. Even though people in high socio-economic status in many countries in Latin-America have healthier diets [52], the obesity prevalence difference between the highest and the lowest wealth index quintile has not changed much in Peruvian women (17% in 2005 vs 16% in 2017), whereas in Bolivian females the difference is slightly larger (14% in 1998 vs 19% in 2008); [53] the same pattern arises with education [53]. Because socio-economic level influences access to healthcare and treatment, a populationwide approach could benefit large populations (e.g., food taxes) or risk-based interventions could focus resources to those who most need them.…”
Section: Public Health Relevancementioning
confidence: 96%
“…There is now a broad consensus on two key issues that need to be addressed: the need for research to focus on generating more data on the amount of FLW outside the current focus area (U.S. and Europe) [7,8], and the need to fully capture estimates of FLW along the complete food supply chain (FSC) [9]. Accordingly, this research aims to contribute to the current scientific literature on FLW in Latin America by calculating the distribution of FLW along the FSC in Peru. So far, little work has been done to have FLW data in Latin American countries, even though hunger is still present [10] and the diet intake quality of crucial food groups commonly related to chronic diseases is deficient [11,12]. Part of this knowledge comes from a study that used aggregated data for 2007 to investigate the per capita quantity of FLW generated in the region, resulting in around 225 kg [13].…”
Section: Introductionmentioning
confidence: 99%